Effect of corrosion of stainless steel welded within lithium chloride - Pereira, Juliete Nathalia; Macêdo Dias, David Márcio; Regone, Natal Nerímio [UNESP]; Fernandes, Marcos A.; Nakamatsu, Sandra; Maestrelli, Sylma Carvalho; Mariano, Neide Aparecida (Trans Tech Publications, 2016)
The difficulties experienced in welding processes of martensitic stainless steel led to development of a new class of them, known as stainless mild martensitic steels. Also, due to the current high demand for energy and materials to oil extraction at great depths, scientists have being developing specific researches about mechanical resistance and corrosion of steels and how these properties are influenced by high temperature processes. This research studies the effect of welding process over the corrosion resistance of the 13Cr4Ni0.02C steel in a lithium chloride solution with a concentration of 120,000 PPM Cl-. The corrosion tests were conducted by cyclic potentiodynamic polarization in the base metal, weld bead and heat affected zone (HAZ) areas of the steel, in average temperatures of 23°C (as reference) and 3°C. The results revealed that the weld bead and heat affected zones of the 13Cr4Ni0.02C steel in a temperature of 3°C are less resistant to corrosion in this environment than the base metal in the same conditions.
Keywords: Cyclic potentiodynamic polarization; Lithium chloride; Martensitic stainless steel; Welding